Walking on Eggshells: An Update on the Stigmatizing of Teen Mothers. Issue 6 (November 2020) - SmithBattle, Lee
Abstract : Abstract: Teen mothers are stigmatized for violating age norms for parenting and for being members of devalued racial or socioeconomic groups. Stereotypes of young mothers perpetuate stigma by teen pregnancy prevention campaigns, television shows, sex education programs, professionals, and the general public. How teen mothers became a stigmatized group; updates on research about their experience of stigma; and resources for reducing stigma are presented. Because stigma is pervasive and has damaging effects, nurses are urged to reduce stigma and discrimination by assuring that health settings are safe and welcoming, and that pregnant and parenting teens are treated with respect and dignity. Doing so is consistent with our professional commitment to promote social justice and mitigate the social inequities that contribute to health disparities for all parents, irrespective of age, gender, ethnicity, immigration status, or income. Abstract : Teen mothers are stigmatized in the media and health care settings. Stereotypes and discrimination contribute to stress, social isolation, and health disparities. Teen mothers are keen to show that they differ from the stereotypical teen mom. A review of stigmatization of teen mothers is presented, along with suggestions for nurses to be supportive and avoid unintentional negative behaviors when caring for teen mothers.